Territorial differences in infant mortality in Latvia in the first decade of the third millennium - Ebela, Inguna; Zile, Irisa; Muciņa, Nadīne; Ražuka-Ebelal, Danute; Rumba-Rozenfelde, Ingrīda (Central European Journal of Public Health, 2015)
OBJECTIVE: Infant and child mortality are some of the most substantial indicators of country welfare. Infant mortality (IM) in Latvia is constantly the highest among 25 Member States of the European Union. Since the regaining of independence in 1991, IM has decreased by almost 50%, however, it is still high enough to cause concern that the country will not be able to meet the UN Millennium Development Goals to decrease IM in Latvia by 2015. The Medical Faculty at the University of Latvia has conducted several studies identifying correlations between IM and GDP, total expenditure on health, unemployment and GINI coefficient. It is necessary to identify all IM causes and relationships which have not been studied, including the effect of social factors causing inequality between inhabitants of urban and rural areas: - The aim of the study was to determine the IM rate and the main death causes and their differences between rural and urban areas in Latvia (2000-2010). MATERIALS: This is a register-based study. The data of 1994 deceased infants was analyzed over the time period from 2000-2010. The studied population was divided into two groups - urban and rural areas by mothers' area of residence. Descriptive and analytical methods were used for analysis - frequency distribution, correlation and regression analysis. RESULTS: IM by maternal residence as well as IM indicators in the most common diagnostic subgroups have been higher in rural areas in the entire studied period (2000-2010). The decrease proportion of IM was more rapid in rural regions with a period average of 6.2% in comparison to urban regions - 2.6%. Annual decrease of IM from perinatal period conditions was 50% lower in rural than urban areas; annual decrease of IM from congenital malformations, deformations and chromosomal abnormalities was 20% lower in urban than rural areas; annual decrease in other diagnostic groups was 40% lower in urban than rural areas. During the study period, differences in infant mortality based on maternal socio- demographic factors, maternal health as well as pregnancy and obstetric history have been found, but the results of statistical analysis cannot be used to define these relationships as statistically significant in either areas. CONCLUSIONS: infant mortality in Latvia due to various conditions prevailing during perinatal period, external causes and sudden infant death syndrome can be substantially decreased - by improving the theoretical and technical capacity of obstetric departments in rural areas as well as educating society on preventable causes of death.
Keywords: novorozenec; Registries; Infant Mortality; Lotyšsko; lidé; Adult; dospělí; Europe; zdraví ve městech; kojenec; Female; registrace; zdraví venkovských oblastí; Urban Health; Latvia; ženské pohlaví; mladý dospělý; Humans; Young Adult; Infant, Newborn; Infant; kojenecká mortalita; Evropa; Rural Health